Contribuição da informação e da tecnologia da informação no processo de abertura de capital das empresas: um estudo de caso - Ponte, Alessandra Varela (2008)
The objective of this study is to identify which is the information technology’s contribution in the Initial Public Offering (IPO) process, in the sense of identify the resources which contributed with the generation of information and helping in the investor decision. Therefore, this study identifies which information is demanded by IPO process, it establishes relations between information and transparency that organizations should own and analyzes which resources and how information technology resources can contribute towards information demanded by IPO process. One of the 10th biggest companies of the state of Ceará, according to Delmiro Gouveia Award, whose IPO process was achieved by Ceará’s professionals, was chosen for the accomplishment of this study. Information about the organization and its attributions in relation to stock market was yielded, identifying which organization’s structure and tools contributed to IPO process. The present study is divided in two main stages. The first one is a bibliographical research about capital market, Controllership, information and information technology. The second one is a research that was applied to the employees who took part in the IPO process of M. Dias Branco organization. The result of the research pointed that Controllership is the department that manages the production of information, verifying possible fails and helping to develop a control mechanism to assure the reliance of information. Beyond that, Controllership uses IT tools to facilitate the accomplishment of the activities. After the described factors were analyzed, it can be perceived that information is a precious asset to decision making and to assure attractiveness to investors. As a result of the research, it can be concluded that tools are needed and organized resources to the demanded information through the IPO which achieve the objective of, help to decision making of internal and external public.